2009
DOI: 10.1073/pnas.0910935106
|View full text |Cite
|
Sign up to set email alerts
|

Temporal latitudinal-gradient dynamics and tropical instability of deep-sea species diversity

Abstract: A benthic microfaunal record from the equatorial Atlantic Ocean over the past four glacial-interglacial cycles was investigated to understand temporal dynamics of deep-sea latitudinal species diversity gradients (LSDGs). The results demonstrate unexpected instability and high amplitude fluctuations of species diversity in the tropical deep ocean that are correlated with orbital-scale oscillations in global climate: Species diversity is low during glacial and high during interglacial periods. This implies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
103
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 60 publications
(117 reference statements)
4
103
2
Order By: Relevance
“…North Atlantic fossil records during the last de-glaciation showed abrupt changes in deep-sea biodiversity associated with a rapidly changing climate (specifically deep-water circulation and temperature) over decadal to centennial time-scales (Yasuhara et al, , 2014. Longer time-scale paleo-ecological studies have also shown systematic changes in faunal structure and biodiversity related to glacial-interglacial climate cycles over the last three million years, and more specifically to climate-driven changes in bottom temperature or particulate organic carbon (POC) flux, depending on the ocean and taxonomic group (Cronin et al, 1996;Cronin and Raymo, 1997;Yasuhara et al, 2009Yasuhara et al, , 2012a. Paleoecology (Yasuhara et al, 2015) has thus revealed the dynamic and sensitive nature of deep-sea ecosystem structure and biodiversity across a wide range of time scales in response to changing climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…North Atlantic fossil records during the last de-glaciation showed abrupt changes in deep-sea biodiversity associated with a rapidly changing climate (specifically deep-water circulation and temperature) over decadal to centennial time-scales (Yasuhara et al, , 2014. Longer time-scale paleo-ecological studies have also shown systematic changes in faunal structure and biodiversity related to glacial-interglacial climate cycles over the last three million years, and more specifically to climate-driven changes in bottom temperature or particulate organic carbon (POC) flux, depending on the ocean and taxonomic group (Cronin et al, 1996;Cronin and Raymo, 1997;Yasuhara et al, 2009Yasuhara et al, , 2012a. Paleoecology (Yasuhara et al, 2015) has thus revealed the dynamic and sensitive nature of deep-sea ecosystem structure and biodiversity across a wide range of time scales in response to changing climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advances in documenting pattern, the underlying drivers that structure diversity and faunal patterns are still controversial (Stuart et al 2003;Carney 2005;Rex et al 2005;Yasuhara and Cronin 2008;Corliss et al 2009;Yasuhara et al 2009b;Tittensor et al 2011). Uncertainty remains in part because these faunal patterns likely have complex causes, reflecting not only species' present-day tolerances for environmental factors (e.g., temperature, productivity) but also spatial and bathymetric differences in speciation, extinction, and dispersal (Rex et al 2005;Jablonski et al 2006), acting within a biogeographic template (McClain et al 2009b;McClain and Barry 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Faunal composition also shows strong depth zonation (Carney 2005), and species diversity usually increases to a mid-bathyal maximum before decreasing again (Rex 1973(Rex , 1981Rex et al 2005;Rex and Etter 2010). Perhaps most surprisingly, many taxa show latitudinal gradients of decreasing alpha diversity from the tropics to the poles, although the gradient may be stronger in the Northern Hemisphere (Rex et al 1993(Rex et al , 2000(Rex et al , 2005Culver and Buzas 2000;Stuart et al 2003;Corliss et al 2009;Yasuhara et al 2009b;Rex and Etter 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6-9). For example, some proposed mechanisms to explain the modern LDG invoke particular climatic conditions that exist today, and the fossil record can be used to evaluate these mechanisms under different climatic conditions in the past (6,(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%